STATISTICAL EVALUATION OF COPD PATIENTS WITH RESPECT TOGENDER: A CROSS-SECTIONAL STUDY - Gökhan Perincek (Baqai Journal of Health Sciences)
This study has been conducted to evaluate chronic obstructive pulmonary disease (COPD) patients in Turkey in terms of gender. This cross-sectional study was performed on 416 COPD patients during January 2014 to January 2016. The various clinical parameters of the patients were obtained from the electronic data bank of the Kars Harakani State Hospital, Kars, Turkey. Patients number of hospitalization, one-year mortality, complete blood cell count, blood gas parameters, and the relationship of these parameters with gender was evaluated. Around 38% of the patients were found to be female. The association of height, body mass index (BMI), and forced expiratory volume in 1 s (FEV1) with gender is found statistically significant (p<0.001). The results further indicated that the association of FEV1 with BMI and weight is directly proportional and FEV1 has a moderate positive correlation with weight and BMI (p<0.001, r=0.250; p<0.001, r=0.371). The association of FEV1 levels with gender are also found statistically significant (p<0.001). FEV1 level are found to be related with smoking status (p<0.001) and co-morbidity (p=0.001) and thus affects in terms of the severity of the disease. No relationship between gender and the outcome of the present hospitalization, mortality or being referred to a more advanced health institution (p=0.202) has been observed. The association of whether mortality occurred or not in a year after the present hospitalization with the gender is statistically significant (p<0.011). The association of C-reactive protein (CRP), platelet, platelet distribution width (PDW), plateletcrit (PCT), hemoglobin, and hematocrit values with gender are also statistically significant (p=0.009, p=0.004, p=0.048, and p<0.001). Eosinophile count has a weak positive correlation with the number of hospitalizations. On the basis of the findings of the study it is concluded that a number of studied parameters affect the severity of COPD and male patients are more affected than females.